Pregnancy and severe anemia: problems in diagnosis and treatment - M. N. Surina; E. A. Chvanova; T. Yu. Marochko; O. B. Karelina (Фундаментальная и клиническая медицина)
Aim. To determine features, course, complications, and outcomes of pregnancy in women with severe anemia.Materials and Methods. We retrospectively analysed 39 case histories of women with severe anemia during pregnancy who delivered in Reshetova Kemerovo Regional Perinatal Center during 2017-2018.Results. Average age of women was 30 ± 5 years (average age of sexual debut 17 ± 1 years). The proportions of primiparous and smoking women were 28% and 56%, respectively. More than two-thirds (69%) of women suffered from chronic anemia before the pregnancy, and 21% were HIVinfected. Average first visit to the obstetrician was registered during the second trimester (at 14 ± 6 weeks of gestation), and 13% did not receive the medical care during the pregnancy. The prevalence of preterm and emergency childbirth was 31% and 69%, respectively; 80% of patients required a Cesarean section, and the average birth weight was 2,820 ± 805 g. Intrauterine growth restriction was observed in 28% of cases. Average values of hemoglobin at the first visit, at hospital admission, and at the time of blood transfusion were 103 ± 13 g/L, 74 ± 8 g/L, and 65 ± 4 g/L, respectively; average serum iron at the first visit and at hospital admission was 11 ± 5 µmol/L and 8 ± 3 µmol/L, respectively. Iron replacement therapy was inefficient in 84% of women who received it (90%).Conclusion. In the majority of cases, severe anemia developed from chronic anemia which had occurred before pregnancy and could not be corrected by means of iron replacement therapy. Pregnant women with severe anemia often require Cesarean section due to pre-eclampsia.